Lessons from the global financial crisis : the relevance of Adam Smith on morality and free markets - Morgan, Richard (Taylor Trade Publishing, 2010)
Adam Smith was an advocate of the free market; however his first and widely-acclaimed work, The Theory of Moral Sentiments, was on ethics. While commentators tend to review this work in isolation from his writing on political economy, Richard Morganargues that although The Wealth of Nations is concerned with political economy, Smith's pointed attacks on exploitation and greed reflect the ethics outlined in his first work and illuminate the constructive role he proposed for government, which includes ensuring the provision of education and protection of society by regulating the banking system.